Faktor yang Mempengaruhi Continuance Intention untuk Menggunakan Pembayaran Elektronik Berbasis Qris - Galih Ilham Ramadhan; Dewita Puspawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the factors influencing continuance intention to use QRIS-based electronic payment systems. A quantitative approach was applied using partial least squares structural equation modeling (PLS-SEM) to examine the relationships among performance expectancy, facilitating conditions, customer satisfaction, and continuance intention to use. Respondents were individuals who had used QRIS more than three times, and data were collected through an online questionnaire. The results indicate that performance expectancy and facilitating conditions have a significant effect on customer satisfaction. Furthermore, customer satisfaction has a significant affects the continuance intention to use QRIS. However, performance expectancy and facilitating conditions do not directly influence continuance intention; instead, their effects are mediated by customer satisfaction. These findings highlight the crucial role of user satisfaction in enhancing the willingness to continue using QRIS.